Ninth Plan (1997-2002) Volume-II Statistical Statement Government of Karnataka - Planning Commission (Planning Commission, 1997)
Plantations, Food, Storage and Warehousing, Agriculture Research & Education , Agricultural Financial Institutions, Marketing & Quality Control, (Other Agricultural Programmes, Special Area Programmes, Command Area Development, integrated Rural Energy Programme, Art and Culture, General Economic Services, Secretariat Economic Services, Survey and Statistics, Capital outlay on other General, District Planning.
Government of Karnataka
Planning, Institutional Finance and Statistics and Science and Technology Department
Keywords: Ninth Plan (1997 - 2002); Annual Plan 1997-98; Outlays; Physical Targets and Achievements; Proposals for Spillover and Ongoing Programmes; Proposals for Maximizing benefits of Completed Programmes; Statement regarding Externally Aided Projects; Basic Minimum Services